Analysis of the Influence of BSB Mobile Application user Experience on Customer Loyalty with Satisfaction as an Intervening Variable - Meta Rianti; Siti Komariah Hildayanti; Shafiera Lazuarni (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
The purpose of this study was to examine if the independent variable of user experience affects the dependent variable, namely customer loyalty, which is mediated through customer satisfaction as an intervening variable. This is a quantitative study with a sample size of 100 respondents based on Hair's Theory in the research population consisting of customers who use the Bank Sumsel Babel Mobile Application. Hypothesis testing demonstrates that user experience has a positive and significant effect on customer satisfaction, with a sig. value 0.000<0.005 and a t value of 13.003. Furthermore, the user experience variable is recognized to have a positive and significant on customer loyalty with a sig. value 0.001<0.005 and a t value of 3.554. Then it was discovered that customer satisfaction had a positive and significant on the customer loyalty variable, with a sig. value 0.000<0.05 and a t value of 4.436. Simultaneously, customer satisfaction has been shown to significantly and positively mediate the influence of the link between user experience and customer loyalty.